Five-year results of Amaze: a randomized controlled trial of adjunct surgery for atrial fibrillation. (26th March 2022) - Sharples, Linda D; Mills, Christine; Chiu, Yi-Da; Fynn, Simon; Holcombe, Helen M; Nashef, Samer A M
Abstract: OBJECTIVES: The Amaze trial showed that adding atrial fibrillation (AF) surgery to cardiac operations increased return to sinus rhythm (SR) without impact on quality of life or survival at 2 years. We report outcomes to 5 years. METHODS: In a multicentre, phase III, pragmatic, double-blind, randomized controlled superiority trial, cardiac surgery patients with >3 months of AF were randomized 1:1 to adjunct AF surgery or control. Primary outcomes of 1-year SR restoration and 2-year quality-adjusted survival were already reported. This study reports on rhythm, survival, quality-adjusted survival, stroke, medication and safety to 5 years. RESULTS: Between 2009 and 2014, 352 patients were randomized. By 5 years 79 died, 58 withdrew, 34 were lost to follow-up and the remaining 182 provided data. AF surgery significantly increased the odds of remaining in SR at 5 years {odds ratio = 2.98 [95% confidence interval (CI) 1.23, 7.17], P  = 0.015}. There was a non-significant decrease in stroke incidence [odds ratio = 0.605 (95% CI 0.284, 1.287), P  = 0.19], but no improved survival [5-year survival: AF surgery 77.3% (95% CI 71.1%, 83.5%), controls 77.8% (95% CI 71.7%, 84.0%), P  = 0.85]. Quality-adjusted survival difference was negligible (−0.03; 95% CI −0.33, 0.27, P  = 0.85). The composite of survival free of stroke and AF was better in the AF surgery group [odds ratio = 2.34 (95% CI 1.03, 5.31)]. There were no other differences. CONCLUSIONS: Adjunct AF surgery confers a higher rate of SR to 5 years and a better composite outcome of survival free of stroke and AF but has no impact on overall or quality-adjusted survival or other clinical outcomes. Clinical trial registration number: ISRCTN82731440. Abstract : Atrial fibrillation (AF) is the most prevalent arrhythmia in patients undergoing cardiac surgery [1].